The Importance of Incorporating Denitrification in the Assessment of Groundwater Vulnerability - Gianluigi Busico; Nerantzis Kazakis; Nicolò Colombani; Khabat Khosravi; Konstantinos Voudouris; Micòl Mastrocicco (Applied Sciences, 2020)
Human activities are deeply connected with groundwater reservoirs, so protecting them from pollution has become a priority in many regions of the world. Nitrate is considered the main groundwater pollutant since it is directly linked to many human activities. Agricultural activities and domestic wastewater have been identified as the main sources of nitrate in groundwater. Nevertheless, there are some natural processes that can mitigate nitrate pollution. Together with dilution processes, the degradation of nitrate through denitrification has been acknowledge as a process that can potentially reduce nitrogen loads, in both deep and shallow aquifers. Usually these processes were not properly quantified in vulnerability assessment methods, until the introduction of LOS indices. In this study, the application of the LOS indices on 4 agricultural areas is discussed, highlighting how the LOS indices can identify portions of the landscape with higher potential denitrification and how they directly enhance the groundwater vulnerability assessment. Previous studies have shown that LOS indices are a valuable tool for proper vulnerability assessment to nitrate, however they need to be coupled with other parameters that also describe nitrate behavior in groundwater. The SINTACS-SVN and DRASTIC-PA methods that include the LOS indices, were applied for the first time in the Epanomi coastal area to evaluate the reliably of the assessment and, despite the different classes range and the weights applied, similar groundwater vulnerability assessment maps were obtained. The nitrate vulnerability maps were comparable with the observed nitrate concentrations and were found to be highly comparable with original LOS maps. Nevertheless, it should be kept in mind that vulnerability methods are only screening tools and groundwater quality observations are pivotal information for environmental management.